2021
DOI: 10.21608/ejchem.2021.93871.4421
|View full text |Cite
|
Sign up to set email alerts
|

Feed Utilization and Lactational Performance of Damascus Goats Fed a Diet Supplemented with Marjoram or Basil Essential Oils

Abstract: Thirty lactating Damascus goats were used to study the effect of marjoram or basil essential oils dietary supplementation on feed utilization and lactational performance. After 7 days of parturition, the goats weighing 41.0±0.8 kg were grouped int three groups 10 goats each using complete random design and fed the experimental treatments included: (1) control diet: consisting of CFM: berseem clover (Trifolium alexandrinum basil oil / kg DM; (3) control diet plus 20 ml marjoram oil / kg DM. Digestibility of DM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Abdullah et al [ 51 ] revealed that lemongrass and roselle herbs supplementation improved milk composition and rumen fermentation without lowering animal performance. Compared to basil essential oil, marjoram essential oil supplementation improved the digestibility of nutrients (dry matter and organic matter), ruminal fermentation (propionic, valeric, and total short-chain fatty acids concentration), milk production, and composition (fat percent, fat corrected milk (4% fat; FCM) and energy corrected milk yields, total solids, fat, and lactose yields, milk efficiency), according to Tawab et al [ 52 ]. Similar results were obtained by Kholif et al [ 53 ] with supplementation of the lactating Boer goats diet with Chlorella vulgaris microalgae with or without copper, as well as Ghoneem and Mahmoud [ 54 ] who found that the supplementation of lactating goat’s diet with thyme leaves or essential oil improved the digestibility but without influencing rumen fermentation parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Abdullah et al [ 51 ] revealed that lemongrass and roselle herbs supplementation improved milk composition and rumen fermentation without lowering animal performance. Compared to basil essential oil, marjoram essential oil supplementation improved the digestibility of nutrients (dry matter and organic matter), ruminal fermentation (propionic, valeric, and total short-chain fatty acids concentration), milk production, and composition (fat percent, fat corrected milk (4% fat; FCM) and energy corrected milk yields, total solids, fat, and lactose yields, milk efficiency), according to Tawab et al [ 52 ]. Similar results were obtained by Kholif et al [ 53 ] with supplementation of the lactating Boer goats diet with Chlorella vulgaris microalgae with or without copper, as well as Ghoneem and Mahmoud [ 54 ] who found that the supplementation of lactating goat’s diet with thyme leaves or essential oil improved the digestibility but without influencing rumen fermentation parameters.…”
Section: Resultsmentioning
confidence: 99%